소비에트 전쟁문학의 흐름과 사회주의 리얼리즘 - 권철근(Kwon Chol-kun) (외국문학연구, 2001)
러시아 전쟁문학의 범위는 매우 광범위하다. 영토 확장을 위한, 또는 보전을 위한 수많은 전쟁을 보여주는 것이 짜르 시대 이래의 러시아 역사이기 때문이다. 치욕적인 몽골과의 전쟁, 뾰뜨르 대제의 스웨덴과의 대북방 전쟁, 어떤 의미에서는 오늘날까지 지속되고 있는 카프카즈에서의 전쟁, 커다란 영토확장을 이루었으나 전투다운 전투가 거의 없었던 시베리아에서의 전쟁, 그리고 나폴레옹과의 대조국 전쟁 등 러시아는 초원지대라는 지형상의 특수성으로 인하여 동서남북 전 방향에서 전쟁을 치루었고, 이러한 전쟁은 러시아 문학의 중요한 배경이 되었다. 인접 국가들과의 이러한 전쟁은 비록 전쟁의 원인과 경과, 그리고 그 결과는 서로 다르기도 하지만, 거의 모든 국가들이 경험했던 것으로, 러시아만의 특수한 역사로 치부할 수는 없을 것이다. 그러나 금 세기의 두 차례에 걸친 세계 대전의 경우는 이전의 러시아에서 일어난 전쟁과는 다른 양상을 보여주었다. 영토의 단순한 확장 및 보전을 위한 전쟁과는 달리, 국가의 존망이 달린 것으로서 그 수행을 위해 국가는 총력을 기울였고, 이러한 노력은 전쟁문학의 발달에 크게 기여하였다. 금 세기의 두 차례 세계대전은 세계적으로 (근대적 의미의) 전쟁문학의 중요한 배경이자 보고(寶庫)가 되었는데, 러시아에서도 예외는 아니었다. 그러나 두 차례의 세계 대전의 경우 러시아는 다른 전쟁 경험국과는 판이하게 다른 역사를 경험하게 되는데, 그것은 제1차 세계대전이라는 대외전쟁과 맞물린 상황에서 국내에서는 볼세비키 혁명과 내전이 발생했기 때문이다. 러시아는 이로 인하여 제 1차 세계 대전으로부터 타의적으로 벗어나게 되었으며, 그리하여 혁명으로 인하여 탄생한 소련 최초의 주된 전쟁문학은 대부분의 다른 나라의 경우와는 달리 외국의 침략자에 맞선 전쟁이 아니라, 혁명과 내전을 배경으로 하여 내부의 적과의 투쟁을 묘사하게된다. 이러한 사실은 소련이 4반세기 후에 경험하게 되는 제2차 세계대전의 경우와도 다른 것으로, 양 차 대전기의 소련 전쟁문학이 그 배경과 형식에 있어서 각기 다른 모습을 보여주는 원인이 되기도 한다. 주지하다시피 러시아의 역사에 있어서 소련 시기는 1917년 10월의 볼세비키 혁명이후로부터 미하일 고르바초프의 1990년의 소련연방 해체 선언에 이르기까지의 70 여년의 기간을 지칭하게 된다. 이 기간 동안 소련은 두 차례의 국가의 흥망이 걸린 전쟁을 경험하게 되는데, 혁명으로 인해 촉발된 내전과 제2차 세계대전이 바로 그것이라는 점은 이미 앞에서 언급한 바와 같다. 소비에트 전쟁문학은 바로 이 두 가지의 상황을 배경으로 하고 있는 것이다. 그러나 두 전쟁문학은 그것의 진행과정에 있어서 서로 상이한 모습을 보여준다. 커다란 차이점 가운데 하나는 제2차 세계 대전을 배경으로 한 작품들은 전쟁수행을 직접적으로 돕기 위한 목적 역시 중요했던 것임에 비하여, 혁명과 내전을 배경으로 하고 있는 내전문학은 실제적으로 내전수행의 목적과는 큰 관련이 없었다는 점이다. The bulk of the Russian war literature appearing in Soviet publications deals with two major time spans in the history of the Soviet Union: the Revolution and civil war and the Second World War. Much of the literature dealing with the wars is written in the spirit of socialist realism. Many works extol the war effort and dedication of Soviet citizens. They emphasize the pride of the people in their army, and promote the ideological and political values advocated by the Communist Party. It is particularly true in the literature dealing with the civil war. It is well known that in the days of Stalin socialist realism was the official method of Soviet literature. The enforced implementation of the rigid principles of socialist realism helped to create the classics of Soviet literature, of which the classics of the civil war literature is a major part. Therefore, the civil war literature becomes not only the classics of Soviet war literature but those of socialist realism. The fact that almost all of the important classics of the civil war literature were published before the public proclamation of socialist realism in 1934 - (1921), <Armored Train 14-69>(1922), (1923), (1927) - indicates the classics of the civil war literature did not follow the existing methods of socialist realism, rather the theories of socialist realism adopted the existing examples of the civil war literature. The volume of literature about the Second World War shows no sign of decline. Some twenty thousand books on this subject had been published in the Soviet Union since the end of the war. But this literature develops and changes. It reacts to the needs of the day because the purpose of war prose is primarily ideological and political, as was true in the case of the civil war literature. Most critics divide the development of the war prose into three periods: the period of the war itself, the post-war era up to the late 1950s, and post-Stalin period up to now. The literature of the first period is mainly didactic and its emphasis is on the atrocities committed by the enemy, and the heroism of Soviet soldiers. The immediate post-war decade was dominated by Stalinism and, therefore, this period had little possibility of creating literature of any artistic merit. In the post-Stalin period a new approach to the subject of war developed with the decline of socialist realism. Likewise, the Soviet literature depicting both the civil war and the Second World War acts as the indicator of the rise and fall of socialist realism. KCI Citation Count: 2